NEW RECORD OF CAMELLIA SECT. CAMELLIA (THEACEAE) FOR THE FLORA OF VIETNAM - Hoang, Thanh Son (Trường Đại học Đà Lạt, 2024)
This study provides color illustrations and describes the morphological characteristics and distribution of Camellia pitardii and Camellia mairei var. lapidea, species formerly considered endemic to China but recently discovered and recorded in the flora of Vietnam.